Analisis Kinerja Petugas Lost and Found dalam Penanganan Bagasi Maskapai Citilink di Bandar Udara Internasional Juanda Surabaya - Muh. Zuhdy Al Ghiffari; Elisabeth Endang Prakosawati (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Baggage handling is a crucial aspect of airline operations, including the lost and found unit, which handles lost, damaged, exchanged, and found baggage issues. At Juanda International Airport in Surabaya, these issues remain common. This study aims to analyze the performance of Citilink's lost and found officers in handling various baggage issues and evaluate the unit's productivity, efficiency, and effectiveness. The method used was descriptive qualitative research with a case study approach, collecting data through observation, semi-structured interviews with officers, and documenting operational procedures and baggage handling reports. The results indicate that lost and found officers play a crucial role in post-flight service, from receiving reports to providing compensation. Although procedures are carried out according to SOPs, obstacles such as a lack of manpower and a manual reporting system slow down the process. Officer performance is quite good, but efficiency improvements and the use of technology are needed, such as further training and a modern baggage tracking system.